STUDI PENANGANAN SAMPAH DI TEMPAT PEMROSESAN AKHIR JATIBARANG BERDASARKAN PERATURAN DAERAH KOTA SEMARANG NOMOR 6 TAHUN 2012 TENTANG PENGELOLAAN SAMPAH - Pradana, Azaria Eda; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Waste handling is one of Semarang Local Governance ways to do the waste management of Semarang. This policy’s implementor is Hygine and Gardens Landscape Agency of Semarang. The purpose of this reasearch is to describe and analyze how the Local Governance of Semarang done the implementation of waste handling at Final Processing Place Jatibarang (TPA Jatibarang) depend on Local Regulation Number 6 in 2012. This research is using a qualitative approache with descriptive type. The Analysis techniques to acquire data through observation, interviews and documentation. This research is looking at five phenomena on this implementations, there are waste sorting, collecting, transporting, processing, and final processing. Waste sorting is the responsibility of household to care and to aware of organic and anorganic waste. Waste Collecting is managed by each district. Waste transporting until Final processing is the responsibility of Hygine and Gardens Landscape Agency of Semarang based on the procedure and the completeness of waste transporting equiments to Final Processing Place Jatibarang by the waste trucks until waste final process to be a methan gas and organic fertilize. Depend on the George C. Edwards III, the driving factor of this implementation are communication, disposition, and bureaucratic structure, meanwhile the inhibiting factor is resources. Local Government of Semarang has been done well based on Local Regulation Number 6 in 2012, even though not optimal yet because both the equipments and the finance resources are limit. So of that, embrace human resources, manage finance for waste handling equipments, also support and teamwork of Government, privat, and people are needed.